Physical appearance and elections: An inequality perspective - Bahamonde Hector; Sarpila Outi (Wiley, 2025)
A consensus seems to exist around physically attractive candidates winning elections more often. Unfortunately, we have limited understanding of how voters assess candidates with socioeconomically (dis)advantageous physical appearances. To bridge this gap, we studied the electoral consequences of candidates looking upper class, middle class, or working class. Using official electoral data for the 2017 Finnish municipal elections and a novel data set based on a representative sample of the Finnish population (N = 7,920), we found that Finnish citizens systematically vote for candidates who look like they have (and do have) upper-class occupations. Furthermore, the data strongly suggest that a systematic electoral penalty exists, particularly for female candidates who look like they have (and do have) working-class occupations.